THE LUTHER OF SHI’I ISLAM - al-Qurtuby, Sumanto (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2012)
This paper examines socio-historical roots of the emergence of the idea of “Islamic Protestantism” within Iranian Shi’i tradition. The central focus of this study is to present thoughts and activities of so-called “Iranian Luthers” as the agents, actors, and prime movers of the birth of Islamic reformation in Iran. These actors whose ideas of Islamic reformation have had great influences and reached broader audiences beyond Iranian territory include Sayyid Jamal al-Din al-Afghani, Ali Shari’ati, Mehdi Bazargan, Hashem Aghajari, and Abdul Karim Soroush. There are a number of Iranian reformers deserve credits for their thoughtful, controversial ideas of Islamic reformations. These Iranian reformers are considered “the Luthers of Islam” for their deep admiration of Martin Luther’s Protestant Reformation, and their calls for Islamic reformation just like Luther did in the sixteenth century Europe. By the socio-historical and descriptive analysis, this paper is not intended to compare two religious reformations in Iran and Europe, but rather to study and analyze their notions with regard to Islamic reformation.***Artikel ini membicarakan tentang akar sosio-historis munculnya gagasan “Protestanisme Islam” dalam tradisi Syi’ah Iran, dengan fokus kajian pemikiran dan gerakan yang disebut “Luther Iran” sebagai agen, aktor, dan penggerak utama lahirnya reformasi Islam di Iran. Ide-ide reformasi Islam memiliki pengaruh besar dan mencapai khalayak yang lebih luas di luar wilayah Iran termasuk Sayyid Jamal al-Din al-Afghani, Ali Shari’ati, Mehdi Bazargan, Hashem Aghajari, dan Abdul Karim Soroush. Sejumlah reformis Iran layak mendapatkan perhatian karena pemikiran, ide-ide kontroversial mereka dalam reformasi Islam. Para reformis Iran dianggap sebagai “Luther Islam” karena kekaguman mendalam mereka terhadap Martin Luther, dan mereka menghendaki reformasi Islam seperti yang terjadi pada masa Luther di Eropa abad keenam belas. Dengan analisis sosio-historis dan deskriptif, tulisan ini tidak dimaksudkan untuk membandingkan dua reformasi keagamaan di Iran dan Eropa, melainkan untuk mempelajari dan menganalisis gagasan-gagasan mereka mengenai reformasi Islam.